PPP GRAMMAR METHOD FOR TEACHING YOUNG LEARNERS - Baratova Dilinura Akramovna (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This article explores the effectiveness of the PPP (Presentation, Practice, Production) method in teaching English grammar to young learners. It discusses the theoretical background, stages of implementation, and practical strategies for classroom use. The paper emphasizes the method’s adaptability, its alignment with children’s cognitive development, and its potential to make grammar learning engaging and meaningful. Key advantages and limitations are examined to provide a balanced view for educators. The study concludes that PPP is a reliable and flexible approach for fostering grammar competence in young language learners.